SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The fate of genes that cross species boundaries after a major hybridization event in a natural mosquito population - Mark J. Hanemaaijer; Travis C. Collier; Allison Chang; Chloe C. Shott; Parker D. Houston; Hanno Schmidt; Bradley J. Main; Anthony J. Cornel; Yoosook Lee; Gregory C. Lanzaro (Molecular Ecology, 2018)
Animal species are able to acquire new genetic material via hybridization and subsequent introgression. However, little is known about how foreign genomic material is incorporated into a population over time and what genes are susceptible to introgression. Here, we follow the closely related mosquito sister species Anopheles coluzzii and Anopheles gambiae in a sympatric natural population in Mali at multiple time points spanning a period of 25 years. During this period, we observed the temporary breakdown of mating barriers, which allowed us to explore the fate of alleles that crossed the species boundary in a natural population. Whole genome sequencing of 74 individuals revealed introgression within only 34 genes (0.26% of total genes) from A. gambiae to A. coluzzii , the majority contained within a 4 Mb region on the 2L chromosome which includes the insecticide resistance gene (AGAP004707). We designed a genotyping assay to follow 25 of the 34 introgressed alleles over time and found that all A. gambiae alleles, except four, reached a frequency of 50% in the A. coluzzii population within 4 years (~50 generations) and increased to ~80% within 6 years (~75 generations). However, the frequency of all introgressed alleles, except three, decreased to ~60% in 2016. This suggests an ongoing process of purifying selection in the population against DNA of foreign ancestry, except for alleles that are under positive selection, resulting in a complex genomic landscape . This study shows that stable introgression is limited to only specific genes even within closely related species.

Complex genome evolution in Anopheles coluzzii associated with increased insecticide usage in Mali - Bradley J. Main; Yoosook Lee; Travis C. Collier; Laura C. Norris; Katherine Brisco; Abdrahamane Fofana; Anthony J. Cornel; Gregory C. Lanzaro (Molecular Ecology, 2015)
In certain cases, a species may have access to important genetic variation present in a related species via adaptive introgression. These novel alleles may interact with their new genetic background, resulting in unexpected phenotypes. In this study, we describe a selective sweep on standing variation on the X chromosome in the mosquito Anopheles coluzzii , a principal malaria vector in West Africa. This event may have been influenced by the recent adaptive introgression of the insecticide resistance gene known as kdr from the sister species Anopheles gambiae . Individuals carrying both kdr and a nearly fixed X‐linked haplotype, encompassing at least four genes including the P450 gene CYP 9K1 and the cuticular protein CPR 125 , have rapidly increased in relative frequency. In parallel, a reproductively isolated insecticide‐susceptible A. gambiae population (Bamako form) has been driven to local extinction, likely due to strong selection from increased insecticide‐treated bed net usage.